Designing a training program in handicrafts Art education students (Journal of the College of Basic Education, 2022)
Today we live in an era that changes rapidly and the phenomenon of material, cultural and spatial progress rises, and the speed of the flow of knowledge and the increase in its applications pose many challenges for educators, so new methods have appeared to benefit from educational strategies, and thus the need arises to design a training program for students of handicrafts in the Department of Art Education by adopting a methodology Correct and clear scientific basis with experimental theoretical foundations through their acquisition of cognitive and motor skills, and for the purpose of achieving the goal of the current research, the researcher sought to:Designing a training program in handicrafts for students of the Department of Art Education, as the researcher relied on one of the experimental designs with two equal groups (experimental and control) with a post-test, because it is suitable for the purpose and hypothesis of the research.